Evolution of the Human Pelvis. Issue 5 (May 2017) - Rosenberg, Karen R.; DeSilva, Jeremy M.
ABSTRACT: No bone in the human postcranial skeleton differs more dramatically from its match in an ape skeleton than the pelvis. Humans have evolved a specialized pelvis, well‐adapted for the rigors of bipedal locomotion. Precisely how this happened has been the subject of great interest and contention in the paleoanthropological literature. In part, this is because of the fragility of the pelvis and its resulting rarity in the human fossil record. However, new discoveries from Miocene hominoids and Plio‐Pleistocene hominins have reenergized debates about human pelvic evolution and shed new light on the competing roles of bipedal locomotion and obstetrics in shaping pelvic anatomy. In this issue, 13 papers address the evolution of the human pelvis. Here, we summarize these new contributions to our understanding of pelvic evolution, and share our own thoughts on the progress the field has made, and the questions that still remain. Anat Rec, 300:789–797, 2017. © 2017 Wiley Periodicals, Inc.